2017
DOI: 10.1093/mnras/stx1683
|View full text |Cite
|
Sign up to set email alerts
|

Off-axis emission of short γ-ray bursts and the detectability of electromagnetic counterparts of gravitational-wave-detected binary mergers

Abstract: We present calculations of the wide angle emission of short-duration gamma-ray bursts from compact binary merger progenitors. Such events are expected to be localized by their gravitational wave emission, fairly irrespective of the orientation of the angular momentum vector of the system, along which the gamma-ray burst outflow is expected to propagate. We show that both the prompt and afterglow emission are dim and challenging to detect for observers lying outside of the cone within which the relativistic out… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
163
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(178 citation statements)
references
References 63 publications
(78 reference statements)
10
163
1
3
Order By: Relevance
“…Instead it must arise from some previously unseen process, such as a heated cocoon (e.g. (26,27)); and we are likely viewing the event off-axis (unless there was no jet at all), as indeed our modelling of the UV emission (above) suggests. In this case, if there is an ultrarelativistic jet which is oriented away from us, we can expect X-ray emission at late times.…”
Section: Afterglow Emissionmentioning
confidence: 82%
See 2 more Smart Citations
“…Instead it must arise from some previously unseen process, such as a heated cocoon (e.g. (26,27)); and we are likely viewing the event off-axis (unless there was no jet at all), as indeed our modelling of the UV emission (above) suggests. In this case, if there is an ultrarelativistic jet which is oriented away from us, we can expect X-ray emission at late times.…”
Section: Afterglow Emissionmentioning
confidence: 82%
“…But even using the observed correlation (14) between E γ,iso and X-ray afterglow luminosity, the predicted X-ray flux at ∆t = 0.6 d is still above our Swift and NuSTAR upper limits. This requires an alternative explanation for the observed γ-ray emission, such as a (typical) short GRB viewed (slightly) off-axis, or the emission from a cocoon formed by the interaction of a jet with the merger ejecta (26)(27)(28). We return to this issue below in the context of late-time (∆t >∼ 10 d) X-ray emission (see also (10) and (9)).…”
Section: The Uv Counterpart Rules Out An On-axis Afterglowmentioning
confidence: 97%
See 1 more Smart Citation
“…Another possibility is that thermal emission is produced by a nearly spherical outflow, which expands at sub-relativistic speeds, the so-called cocoon (Lazzati et al 2017;Kasliwal et al 2017). The peak energy and the luminosity constrain the size of the emitting region to be ∼ 2 × 10 7 cm.…”
Section: Constraints On Thermal Emissionmentioning
confidence: 99%
“…Indeed, Troja et al (2017), interpret an off-axis afterglow via an observed delay in the X-ray emission. Additionally, a slowly expanding cocoon can also be formed by the material pushed away during the propagation of the jet (Lazzati et al 2017).…”
Section: Introductionmentioning
confidence: 99%